Comparative Study of Single and Composite Nanolubricants in Automotive Air-Conditioning (AAC) System Performance. (January 2019) - Hamisa, A H; Azmi, W H; Zawawi, N N M; Sharif, M Z; Shaiful, A.I.M.
Abstract: Various studies by leading experts have shown the effectiveness of nanolubricant in improving the performance of the automotive air conditioning (AAC) system. Along with the advancement of technology, composite nanolubricant have been introduced and have been proven to have better properties than normal nanolubricant. The Al2 O3 -SiO2 /PAG composite nanolubricant have better stability, better heat transfer, and improve tribology characteristic compare to its individual single nanoparticles nanolubricant. However, until now no experiments were conducted to test the effectiveness of composite nanolubricant in the AAC system. An experimental study is then taken by testing the Al2 O3 -SiO2 /PAG in AAC system. The results of this experiment have been compared with results of the previous study that uses Al2 O3 /PAG and SiO2 /PAG in AAC system. It is found that the composite nanolubricant have a high enhancement in the COP and does reduce the compressor work of the AAC system. The comparison between Al2 O3 -SiO2 /PAG, Al2 O3 /PAG and SiO2 /PAG nanolubricant demonstrates that Al2 O3 -SiO2 /PAG, has better performance in term of compressor work reduction and COP enhancement at an average of 28.7 % and 31.64 %, respectively. At last, it was recommended to use the Al2 O3 -SiO2 /PAG nanolubricant for application in AAC system.